THE ANALYSIS OF SERVICE MANAGEMENT BASED INFORMATION TECHNOLOGY SYSTEMS AT PT MITRA SOLUSI TELEMATIKA - Oktapiani, Eka (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
Service Point is the spearhead that connects between the customer with the workforce engineer in the process of information technology services to improve IT services in the company. Often companies ignore this, whereas service point is one of the services of information technology services in order to ensure the sustainability of the business offered by the company. Analysis of incident management system in ITOP program and IT services service based on ITIL V3 framework for Service Point at PT Mitra Solusi Telematika is very much needed in effort to improve IT service to support Vision of PT Mitra Solusi Telematika become provider of integrated technology solution. One effort to improve IT services is by developing the process of providing IT services and services as a single point of contact that bridges between customers with all service point staff and IT services. The development of incident ITOP program management and IT support analysis begins with gathering information and analysis through a review of processes within existing ITOP programs, and ITIL V3 framework literature study. Analysis is done to refine the existing process. Once the document is created and developed, the next step is the document verification process to find out the purpose of the incident management process has been met. The results of this development of the management can facilitate the needs and improve IT services especially in Service Point Department PT Mitra Solusi Telematika for IT services to be maintained and measurable